Investigation of Fresh Gastric Normal and Cancer Tissues Using Terahertz Time-Domain Spectroscopy - Grigorev, Roman (Materials (Basel), 2019)
In recent times, terahertz (THz) technologies have been actively applied in many biomedical research work, including gastric cancer diagnosis. In order to provide an effective removal of tumor during surgery, it is necessary to clearly distinguish it from different membranes of the stomach. In this work, we reported an investigation of various normal and cancer fresh gastric tissues using terahertz time-domain spectroscopy in the reflection mode. Refractive index and absorption coefficient of moderately differentiated and poorly differentiated gastric adenocarcinomas, as well as both serosa and mucosa were obtained in the frequency range from 0.2 to 1 THz. All cancer tissues were distinguishable from normal ones. The influence of the morphology of the investigated tissues on the obtained optical properties is discussed. The obtained results demonstrated a potential of THz time-domain spectroscopy to discriminate a tumor from normal serous and mucous gastric membranes. Thus, this method might be applied to gastric cancer diagnosis.